2009
DOI: 10.1111/j.1468-2885.2009.01348.x
|View full text |Cite
|
Sign up to set email alerts
|

An Economic Theory of Political Communication Effects: How the Economy Conditions Political Learning

Abstract: Politics and economics are inextricably linked. This article argues that the economy has been an underdeveloped contextual variable capable of coordinating the process and consequences of political communication. A theoretical model connecting microindividual outcomes to macrosocial functioning is proposed to capture the dynamic ecology of citizens' political involvement. In particular, the economic environment is theorized to impact voters' news media use and political learning through a series of mechanisms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 110 publications
(124 reference statements)
0
8
0
1
Order By: Relevance
“…Three arguments may be made for the economy's primary role in understanding information acquisition during an economic crisis (Shen 2009). For one, the economy is essentially a valence issue, such that all citizens support economic prosperity and are alarmed when the economy plummets.…”
Section: Information Acquisition During Economic Downturnsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three arguments may be made for the economy's primary role in understanding information acquisition during an economic crisis (Shen 2009). For one, the economy is essentially a valence issue, such that all citizens support economic prosperity and are alarmed when the economy plummets.…”
Section: Information Acquisition During Economic Downturnsmentioning
confidence: 99%
“…Second, an economic recession is likely to trigger alarm among the public and generate grievances about the management of the economy. Such alarm can motivate citizens to seek further information in order to sanction incumbent governments for mismanagement of the economy (Shen 2009). A number of studies have shown that information seeking tends to increase with the onset of intense political events that trigger alarm among the general public (Bennett & Paletz 1994;Page & Shapiro 1992;Prior 2002).…”
Section: Information Acquisition During Economic Downturnsmentioning
confidence: 99%
See 2 more Smart Citations
“…Naturally, even if the information conveyed by the media does not always accurately reflect the economic situation (Hetherington, 1996), the actual circumstances do have an impact on its tone (Shen, 2009). We therefore first provide an overview of the state of the Israeli economy at the time the study was conducted (the first part of 2010).…”
Section: Actual Economic Circumstances and Their Impact On Economic Mmentioning
confidence: 99%